Chytridiomycosis: a Devastating Emerging Fungal Disease of Amphibians - Paula, Catia D. De; Catão-Dias, Jose L. (Brazilian Journal of Veterinary Pathology, 2011)
Amphibians have suffered the most striking declines among all vertebrates. Infectious diseases are one of the causes and Chytridiomycosis, caused by the fungus Batrachochytrium dendrobatidis (Bd) is considered the most concerning one. This emerging infectious disease infects a broad variety of amphibians and is considered responsible for numerous declines and extinctions of these animals. Bd has been reported all over the world including Brazil in captive and free living species of amphibians. The origin of this pan-epizootic is unkown. Major histopathological findings include epidermal hyperkeratosis, hyperplasia, and focal necrosis of epidermal cells. The cause of death may be by disruption of ion equilibrium. The chytrid infection may be diagnosed with methods such as histopathology, immunohistochemistry, electron microscopy, conventional PCR, real-time PCR, and nested PCR. The most used treatment is daily baths of itraconazole at 0.01% for five minutes during 11 days. This has been successfully used to treat chytridiomycosis in a few amphibian species. Disinfection protocols are essential for the management of chytridiomycosis in captivity and in the wild. This is an important disease to be studied in Brazil due to the devastating effects that it can cause in amphibians populations.